Beyond Utility: Habitual Dynamics in Mobile Payment Continuance Post-Pandemic – An Extension of Technology Continuance Theory - Indra Fata Raharja; Charissa Nurkhayla Sutanto; Sarah Qonitah; Willy Gunadi (Journal of Business, Social and Technology, 2026)
Background: The rapid adoption of digital payment services in Indonesia surged during the COVID-19 pandemic, reaching 96% population penetration by 2024. However, a critical research gap exists: most studies focus on initial adoption, leaving post-pandemic continuance behavior—particularly the role of habit—underexamined. This study addresses this gap by investigating post-adoption mobile payment continuance through the Technology Continuance Theory (TCT), extended with habit as a moderating variable. Objective: The objective of this study is to explore the factors influencing users’ continuance intention to use digital payment services in Indonesia after the COVID-19 pandemic. It aims to incorporate habit as a moderating variable within the TCT framework. Methods: Data were collected from 264 urban respondents who have consistently used digital payment services since the pandemic. A partial least squares structural equation modeling (PLS-SEM) approach was employed to analyze the data and test the proposed model. Results: The study found that user attitude, satisfaction, and perceived ease of use significantly influence continuance intention. Additionally, confirmation of usage experience positively impacts satisfaction and perceived usefulness. Interestingly, perceived usefulness does not directly influence continuance intention. The study revealed that habit plays a dual role: it strengthens the relationship between perceived usefulness and continuance intention while weakening the influence of satisfaction. Conclusion: The findings suggest that habit significantly affects post-adoption behavior, shifting the decision-making process from deliberate to automatic. Practical implications for fintech providers include fostering habit formation through personalization and satisfaction monitoring. This study extends TCT by integrating habit as a crucial moderating factor in continuance intention.